Ambivalensi dalam Mencari Sarang Angin - Yulitin Sungkowati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This paper aims at explaining the ambivalences in the novel Mencari Sarang Angin (MSA) written by Suparto Brata. The ambivalences found in MSA are seen not only in the space and time movement, but also in the dialects of European (Dutch) and Javanese culture. The space and time movement points back at a space and time that will be left. Although the European culture is placed in a higher position as compared to Javanese culture, it can't move up Javanese culture easily. In relation to the position between European and Javanese, or between the colonialist and the colony, the ambivalences have occured not only between receiving European logic and keeping Javanese philosophy and between receiving democratic values and feudalism, but also between monogamy and polygamy marriage. The relation is not one that ignores each other, but it the one that creates third space, it is the hybrid of Javanese and European culture.